A New SteatoScore in the Evaluation of Non-Alcoholic Liver Disease in Oncologic Patients - Cioni, Dania; Gabelloni, Michela; Sanguinetti, Andrea; De Rosa, Laura; Aringhieri, Giacomo; Tintori, Rachele; Candita, Gianvito; Febi, Maria; Faita, Francesco; Lencioni, Riccardo; Neri, Emanuele (Frontiers in Oncology, 2022)
Purpose: To evaluate reproducibility of a new multi-parametric steatoscore (new SteatoScore) in oncologic patients with non-alcoholic fatty liver disease (NAFLD) and to compare it with computed tomography (CT). Material and methods: Fifty-one (31 males, 20 females) oncologic patients, with a mean age and weight of 63.9 years and 78.33 kg, were retrospectively enrolled in the study. Patients underwent ultrasound (US) and computed tomography (CT) examinations as part of their oncologic follow-up protocol. US examinations were performed by using a 3.5 MHz convex probe. During the US examination, three standardized clips were obtained in each patient. Two operators performed all measurements, one of whom repeated the processing twice in one year. Hepatic/renal ratio (HR), attenuation rate (AR), diaphragm visualization (DV), hepatic/portal vein ratio (HPV), and portal vein wall visualization (PVW) were acquired and calculated by using Matlab and inserted in a multi-parametric algorithm called new SteatoScore. On unenhanced CT scan, hepatic attenuation (HA), liver-spleen difference (L-S) and liver/spleen ratio (L/S) were measured by placement a region of interest (ROI) within liver and spleen parenchyma avoiding areas with vessels and biliary ducts. Results: The intra-observer variability was greater than the inter-observer one, with intraclass correlation coefficient (ICC) values of 0.94 and 0.97 respectively. Correlation between single US and CT parameters provided an agreement in no case exceeding 50%. New SteatoScore showed high reproducibility, and high coefficient of correlation with L-S (R=-0.64; p<.0001) and L/S (R=-0.62; p<.0001) at CT. Conclusion: New SteatoScore has a high reproducibility and shows a good correlation with unenhanced CT in evaluation of oncologic patients with NAFLD.